2009
DOI: 10.1111/j.1468-1331.2009.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

An educational multimedia campaign improves stroke knowledge and risk perception in different stroke risk groups

Abstract: Our data indicate that educational programs and the introduction of stroke risk factors can increase stroke risk perception in the public. Even though some risk groups (smokers, obese) reveal a ceiling effect, future campaigns should focus on high risk populations remarkably underrating their risk, like those with coronary heart disease or the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…These findings suggest that economic constraints predict less PA, consistent with previous reports that PA was predicted by education 16,18 and socioeconomic status. 19,20,36 Only 20% of our sample smoked some days or every day, comparable to the smoking rate for women in the same age group statewide (18.5%). 26 In our study, fewer women younger than 46 years reported smoking (16.9%) than those older than 46 years (23.7%).…”
Section: Discussionsupporting
confidence: 63%
“…These findings suggest that economic constraints predict less PA, consistent with previous reports that PA was predicted by education 16,18 and socioeconomic status. 19,20,36 Only 20% of our sample smoked some days or every day, comparable to the smoking rate for women in the same age group statewide (18.5%). 26 In our study, fewer women younger than 46 years reported smoking (16.9%) than those older than 46 years (23.7%).…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, we showed that educational effects and stroke risk perception varied considerably in different risk groups [26]. The evaluation of further sex-specific aspects in stroke education seems mandatory, while evidence on differences in stroke aetiologies and outcome as well as prevention strategies is steadily growing.…”
Section: Discussionmentioning
confidence: 97%
“…1,2,28 Only a few interventions have been designed and tested at the community level to both increase public stroke knowledge and impact behavior that will lead to earlier hospital arrival for treatment. 2,[29][30][31][32][33][34] Most of these studies have shown that community-based education campaign interventions using the media can increase community awareness of the warning signs for stroke and the need to activate EMSs when these symptoms develop.…”
Section: Need For Improved Ems Activation In Stroke Carementioning
confidence: 99%